English Reading Strategies and Proficiency among Senior High School Learners - Mokhammad Nizzam (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2016)
This study attempts to investigate: 1) kinds of reading strategies employed by Indonesian senior high school students, 2) whether there is a significant difference between poor and good readers in using reading strategies; and 3) if there is a significant relationship between students’ English reading strategies and reading proficiency. Using descriptive quantitative and correlational design, this research involved 100 twelfth grade students of Madrasah Aliyah PP. Amanatul Ummah, Mojokerto, East Java. They were asked to complete a five-point Likert scale questionnaire comprising 44 reading strategy item and self-assessment rubric on their reading proficiency. To achieve the three goals, the data was analyzed using Principal Component Analysis, Independent Sample t-Test, and Pearson Correlation via SPSS 21. The result revealed eight strategy components named to be memory, elaboration, planning, organization, regulating, social, affective, and compensation. Further analysis showed the significant difference between poor and good readers in using reading strategies with t.value of 5.06 and sig.t.test of .000. The study also discovered a significant correlation between English reading strategies and reading proficiency of. 394 and p.value is 0.00.